TREATMENT AND PREVENTION OF VAGINAL CANDIDASIS IN MEDICINE (LITERATURE REVIEW) - Aminjon S. Ne’matov; Venera Q. Absattarova; Nodira T. Yodgorova; Mashhura I. Nabiyeva (Central Asian Journal of Medicine, 2024)
In the analysis of this literature, general information about vaginal candidiasis, the relevance of the disease, symptoms, treatment and prevention, the fungus that causes this disease types, in particular, general information about the type of Candida albicans, etiology, diagnosis of this type about, How does acquired immunodeficiency virus (HIV) cause infectious vaginosis stimulation, the importance of the reduction of probiotics in pregnant women in the development of the disease, the estrogen hormone in women effect of the frequency of change on the disease, different in the metabolism of acids the effect of changes on Candida albicans, resistance of the species to various substances, vaccination work, this fungus and o on the disease conducted experiences of recent years, in particular, the effect of antifungal drugs such as nystatin, amphotericin, fluconazole, clotrimazole, their reception and according to instructions and so in theoretical and practical medicine in this field news of recent years information about planned and analyzed and the results are widely reported.